Water Quality Bioassessment Using Macrozoobenthos In The Batang Arau River, Padang City - Saidina Bima; Izmiarti Izmiarti; Nofrita Nofrita (Jurnal Biologi Universitas Andalas, 2022)
Research on Water Quality Bioassessment Using Macrozoobenthic in the Batang Arau River, Padang City was carried out in March - September 2021. This study aims to determine the composition and structure of the macrozoobenthic community and water quality in the Batang Arau River based on the BMWP-ASPT index. This research uses the survey method and station determination by purposive sampling, based on environmental conditions. Macrozoobenthic samples were collected by using Surber net 30x30 cm2 and Eckman grab 15x15 cm2, and physical and chemical factors were also measured. The results showed that the macrozoobenthic communities found in the Batang Arau River were 37 genera with the composition of 6 genera Gastropods, 28 genera Insect, 2 genera Hirudinea, and 1 genus Oligochaeta. The total density of macrozoobenthic ranged from 140-1775 ind/m2 with the highest density at Station V and the lowest at Station III. The predominant genus (KR ≥ 10%) found at each station varied, Station I and Station II were Orthocladius and Caenis; Station III was Polypedium, Orthocladius, Baetis, and Elophila, Station IV was Orthocladius, Caenis, Erpobdella, Hellopdella, and Tubifex, and Station V was Melanoides. The diversity index of macrozoobenthic (H') in the Batang Arau River was 2.38 ranging from 0.5-2.57 classified as low to moderate, and the distribution of the macrozoobenthic population (E) is 0.65, ranging from 0.25-0.8 classified as uneven to equally. The water quality in the Batang Arau River based on the BMWP-ASPT index at Stations I and II are classified as unpolluted, Station III was lightly polluted, Station IV was moderately polluted, and Station V was heavily polluted.